Розпаралелювання програм на фортрані з використанням техніки переписувальних правил - Doroshenko, A.Yu.; Zhereb, K.A.; Tulika, E.M. (Інститут програмних систем НАН України, 2015)
We describe an approach to parallelize Fortran programs based on rewriting rules technique. We use GCC compiler to parse Fortran source code which allows processing code in older versions of Fortran. We have applied our approach to parallelize an applied problem from quantum chemistry domain. The results of computational experiments demonstrate efficiency of proposed approach.